2020
DOI: 10.1021/acsnano.9b06860
|View full text |Cite|
|
Sign up to set email alerts
|

Use of EpiAlveolar Lung Model to Predict Fibrotic Potential of Multiwalled Carbon Nanotubes

Abstract: Expansion in production and commercial use of nanomaterials increases the potential human exposure during the lifecycle of these materials (production, use, and disposal). Inhalation is a primary route of exposure to nanomaterials; therefore it is critical to assess their potential respiratory hazard. Herein, we developed a three-dimensional alveolar model (EpiAlveolar) consisting of human primary alveolar epithelial cells, fibroblasts, and endothelial cells, with or without macrophages for predicting long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 81 publications
0
74
0
2
Order By: Relevance
“…Direct exposures of fibroblasts to CNTs stimulated progressive cell proliferation or collagen production, the known fibrotic markers [25,26]. Submerged exposure of fibroblasts, epithelial cells, and macrophages used in the presented study was previously used as a first screening tool, and it was shown that exposure to CNTs can induce proinflammatory and profibrotic responses [27,28] An increased proinflammatory response upon repeated exposure to CNT aerosols was also observed in a 3D lung co-culture model (in the presence of immune cells) consisting of cell-lines [29] or primary cells including fibroblasts [30].…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…Direct exposures of fibroblasts to CNTs stimulated progressive cell proliferation or collagen production, the known fibrotic markers [25,26]. Submerged exposure of fibroblasts, epithelial cells, and macrophages used in the presented study was previously used as a first screening tool, and it was shown that exposure to CNTs can induce proinflammatory and profibrotic responses [27,28] An increased proinflammatory response upon repeated exposure to CNT aerosols was also observed in a 3D lung co-culture model (in the presence of immune cells) consisting of cell-lines [29] or primary cells including fibroblasts [30].…”
Section: Introductionmentioning
confidence: 69%
“…The underlying drive behind the development of an inflammatory response is to clear the foreign material from the tissue and to eventually initiate the repairing pathway, which is facilitated by growth factors, such as the TGF-β. TGF-β was used as a positive fibrotic control because of its involvement in the development of fibrosis in different organs, disturbances of the homeostatic microenvironment, promotion of cell activation, migration, invasion, and excessive extracellular matrix production [30,46]. No statistically significant increase for any of the cytokine release measurements was observed at any exposure time-points upon exposures to any of the tested materials.…”
Section: Profibrotic Responsementioning
confidence: 99%
See 2 more Smart Citations
“…[63] In theory, by enabling analysis of each KE (e.g., pro-inflammatory mediator release, cell proliferation, pro-fibrotic mediator release, collagen production), it is possible to use an in vitro model to determine if it predicts the KE(s), and thus the AO. Recently, a study by Barosova and colleagues [64] used AOP173 to assess the pro-inflammatory and pro-fibrotic impacts of different multi-walled CNTs upon an advanced in vitro lung cell system. These approaches are starting to lay the foundation for the use of (advanced) in vitro models to predict the hazardous outcome of human exposure to specific xenobiotics, such as ENMs.…”
Section: How Predictive Are In Vitro Models For Toxicology Testingmentioning
confidence: 99%